BML-111 alleviates inflammatory response of alveolar epithelial cells via miR-494/Slit2/Robo4 signalling axis to improve acute lung injury - Fang Zou; Zhong-Bao Zhuang; Shuang-Shuang Zou; Bu Wang; Zhi-Hua Zhang (Taylor & Francis Group, 2022)
Acute lung injury (ALI) is a common, variously induced lung cell injury with high mortality. It is also an early stage of acute respiratory distress syndrome. BML-111 is a lipoxin A4 receptor agonist that plays an important role in inflammation. However, its function on ALI remains unclear. To explore whether BML-111 is involved in ALI and its regulatory molecular mechanism, we constructed an in vitro ALI model by stimulating primary mouse alveolar epithelial cells (AECs) with lipopolysaccharide (LPS). The downstream target of microRNA (miR)-494 was predicted by Targetscan. The apoptosis and expression of inflammatory cytokines were analysed by RT-qPCR, Western blot, and ELISA. BML-111 treatment alleviated LPS-induced apoptosis and the production of inflammatory cytokines, such as tumour necrosis factor α, interleukin (IL)-6, IL-1β, in primary mouse AECs via downregulating miR-494. MiR-494 targeted and downregulated slit guidance ligand 2 (Slit2) in primary mouse AECs. BML-111 activated the Slit2/roundabout guidance receptor 4 (Robo4) axis via downregulating miR-494 to reduce LPS-induced damage in AECs. This study elucidated that miR-494 on BML-111 alleviated LPS-induced ALI in primary mouse AECs via downregulating miR-494 and subsequently activating the Slit2/Robo4 axis. These findings provided a new idea for the prevention and treatment of ALI and respiratory distress syndrome.